The Implications of Online Banking on Financial Inclusion in Banking Institutions: A Literature Review - Gakuru, Edison; Adyanga, Akena Francis; Ocan, Johnson (East African Nature and Science Organization, 2025)
The study aimed at understanding the implications of online banking on financial inclusion in banking institutions: A literature review on challenges and opportunities. It presents the challenges and opportunities of online banking globally. This study utilized a literature review approach. A comprehensive search was conducted across various academic databases, including Web of Science, Scopus, Dimensions, Google Scholar, and JSTOR, yielding a total of 563 documents. The search was performed using keywords such as “online banking,” “financial inclusion,” “digital banking challenges,” “financial inclusion opportunities,” and “banking institutions.” Boolean operators (e.g., “AND,” “OR”) were used to refine search results and retrieve relevant literature. After filtering, 31 documents were selected for in-depth review based on relevance to the study’s objectives, as evidenced in the reference section. This was after the inclusion and exclusion criteria to ensure the selection of pertinent literature. It was revealed that online banking has transformative potential to advance financial inclusion by making financial services more accessible and affordable. However, it faces challenges that can hinder its impact, including limited digital literacy, high transaction fees, and inadequate infrastructure in certain regions. Therefore, financial institutions should also work to reduce transaction costs and simplify online banking interfaces to accommodate users with low digital skills. Collaboration with financial firms could provide innovative solutions to these issues and improve service delivery